Rope Jumping and Tabata Exercise Effect on Lung Function and Physical Fitness Index - Stella Tinia Hasianna; Oeij Anindita Adhika; Kartika Dewi; Adra Taufiqah; Ajeng Mira Ayuningsih (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Routine physical exercise is often used as an intervention to improve lung function and optimal lung function will improve physical fitness. This study aimed to examine the effect of rope jumping and Tabata exercise in lung function as represented in Forced Expiratory Volume in 1 Second (FEV1), Forced Vital Capacity (FVC) and physical fitness index. Methods: This is an analytic comparative experimental study with pretest and posttest design, involving 60 adult male, separated into 2 groups, which are rope jumping or Tabata exercise for 2 weeks period. The study was conducted at the Faculty of Medicine of Maranatha Christian University Bandung in December 2017 to September 2018. The measured data were FEV1 and FVC using spirometry; and physical fitness index using Harvard Step Test. Data with normal distribution was analyzed using paired T Test, data with abnormal distribution using Mann-Whitney Test, and between group analysis using unpaired T Test. Result: We found a significant increase in FEV1 (P=0.017) but not FVC (P=0.151) in rope jumping grup, and a significant increase in FEV1 (P=0.010) and FVC (P=0.014) in Tabata exercise group. Both physical fitness index in rope jumping group and Tabata exercise group increase significantly (P=0.0005). There are no significant difference between rope jumping and Tabata exercise group in the effect towards FEV1 (P=0.853), FVC (P=0.876) and physical fitness (P=0.545). Conclusion: Rope jumping and Tabata exercise increase lung function and physical fitness index.